2020
DOI: 10.1016/j.heliyon.2020.e04067
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of inhaled dust by workers and suspended dust for pollution control change and ergonomic intervention in metal casting industry: A cross-sectional study

Abstract: Metal casting industry including is an industry which produce high dust pollution (fly ash). Improvements in the form of ergonomic interventions have been carried out by many companies, but do not guarantee all parameters run well. The total indoor suspended dust (TSP) measurement results are not enough to guarantee healthy working conditions. Additional assessment of workers' inhaled dust is needed to change pollution control and work improvement to ergonomics. The design of this study is Cross Sectional Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 59 publications
(54 reference statements)
0
9
0
Order By: Relevance
“…The dust from the gamelan production process is high enough so that it can affect the health of workers if allowed to continue. Dust will be a problem for the health of workers so it is necessary to provide an immediate solution [11], [12]. Therefore it is necessary to have an ergonomic intervention as a solution to this problem.…”
Section: Environmental Conditionsmentioning
confidence: 99%
“…The dust from the gamelan production process is high enough so that it can affect the health of workers if allowed to continue. Dust will be a problem for the health of workers so it is necessary to provide an immediate solution [11], [12]. Therefore it is necessary to have an ergonomic intervention as a solution to this problem.…”
Section: Environmental Conditionsmentioning
confidence: 99%
“…Air pollution has been identified as a major environmental problem associated with respiratory disease and reduced life expectancy. 1 One indicator of reduced air quality is the presence of particulate matter (PM) which is commonly found around industrial activities, such as the cement industry. 1 , 2 In China, the second-largest source emitter of air pollution, a cement factory contributed about 15% CO 2 and 14% of PM <2.5 μm (PM 2.5 ).…”
Section: Introductionmentioning
confidence: 99%
“… 1 One indicator of reduced air quality is the presence of particulate matter (PM) which is commonly found around industrial activities, such as the cement industry. 1 , 2 In China, the second-largest source emitter of air pollution, a cement factory contributed about 15% CO 2 and 14% of PM <2.5 μm (PM 2.5 ). 3 In Romania, the cement industry released about 1 500 000 tons of municipal waste in 18 cities in 2004–2013, including carbon dioxide (CO 2 ), hydrogen chloride (HCl) and hydrogen fluoride (HF) emission.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation and control of dust hazards deserve particular attention in order to decrease the exposure level. Based on previous research studies, workers have reported respiratory discomfort due to the poor air quality in the foundry work environment [3,4]. The presence of particulate matter (PM) in the air may cause serious health problems.…”
Section: Introductionmentioning
confidence: 99%